Timely initiation of complementary feeding and associated factors among mothers having children aged 6 to 24 months in North-West Ethiopia: a comparative cross-sectional study - Tilahun Kegne; Yihun Mulugeta Alemu; Gizachew Tadesse Wassie (BMC, 2024)
Abstract Background The timely introduction of complementary foods during infancy is necessary for nutritional reasons, and to enable the transition from milk feeding to family foods. In the past years, despite efforts that have been put to increase the utilization of timely initiation of complementary feeding practice in Ethiopia, improvements are not satisfactory. Objective To compare the prevalence of timely initiation of complementary feeding and its associated factors among mothers who have Children 6-24 months in Debre Tabor town and rural Farta district, North-west Ethiopia, 2021. Methods A community-based comparative cross-sectional study was employed from December 1/2020 to 30/ 2020 among 1100 mothers. Data were collected using a structured questioner and analyzed using Statistical Product and Service Solutions. Logistic regression analysis with a 95% confidence interval carried out to determine the association between explanatory and the outcome variables. A P-value of < 0.05 was considered statistically significant. Results The prevalence of timely initiation of complementary feeding among urban and rural mothers was 69.8% with (95% CI: 66%, 74%) and 51.9% with (95% CI: 48- 56%) respectively. Urban residence [AOR = 1.39, 95% CI: (1.02-1.94)], had antenatal care visits [AOR = 0.24 (95%CI: (0.13, 0.44)], had post natal care checkups [AOR = 0.44, 95%CI: (0. 27- 0.72)] and being a governmental employee [AOR = 2.82; 95% CI: (1.91-6.1)] were factors associated with timely initiation of complementary feeding among urban mothers. Whereas in rural settings: institutional delivery [(AOR = 2.21, CI: 1.35-3.65)], post natal care checkups [(AOR = 0.53, CI: (0.36-0.77)] being daily laborer [AOR = 3.47; 95% CI: (1.78-6.75)] were associated with timely initiation of complementary feeding. Conclusion The prevalence of timely introduction of complementary feeding in children aged 6-24 months is still low in the study areas. There was also disparity between urban and rural mothers in which urban mothers practiced better.